On the legitimacy of cultural policies: analysing Québec's cultural policy with the Economies of Worth. Issue 1 (2nd January 2017) - Lemasson, Gaëlle
Abstract : This paper explores the question of the legitimation of cultural policies by examining the case of the Canadian French-speaking province, Québec, where the consensus over the legitimacy and the purpose of a cultural policy was not easily reached. To understand the evolution of the justifications for state intervention in this field, we have analysed three major policy statements issued by the government of Québec as well as the criticisms levelled at the moment of their publication using the analytic framework the Economies of Worth. Developed by French sociologist Luc Boltanski and economist Laurent Thévenot, this framework conceptualises different regimes of justification that can be retraced in cultural policy statements. We explore more particularly the concept of 'compromise' which enables us to understand why cultural policies have difficulty achieving consensus. This paper thus aims at assessing the heuristic value of this interpretative device for cultural policy analysis.